Case Study to Improve the Growth of RIT Auto-Care - Chavan, Randhir Y.; Desai, Pravin A.; Thorat, Mahesh J.; Sargar, Rajendra S. (Journal of Engineering Education Transformations, 2021)
In a rural area, vehicle washing and servicing always been done in a traditional way, either the technologies required are not easily available nor are affordable. But as a profound institute, we saw a vision to give customers the service with high-end technologies and at a low cost. Then after we department of Automobile engineering at RIT started the vehicle washing and serving center back in 1983. We kept customers always at the apex and strived to upgrade our servicing center. We refined the undergoing work and made standard operating procedures and started monitoring the activities weekly. Also, we started doing a market survey of what the customers really wanted from such a facility in order to enhance the overall performance of their vehicles at a low cost. We went nearby washing centers to look at what facilities are there? We thought that if we able to provide our customers one- stop solution in vehicle servicing and validation of its performance then definitely the customers will attract and they will get what they want in single visit. As part of up-gradation we successfully commissioned and running an online PUC center and new washing accessories such as vacuum cleaner, established new river water connection and installed CCTV. These facilities add value in servicing and validation of performance of the vehicle in low cost also these facilities are the part of student’s curriculum so our students are getting great exposer to such advanced technologies and they will have hands-on as well. So with this up-gradation we do consultancy work of servicing and validation of the performance of the vehicle at a low cost along with the student’s development.